1999
DOI: 10.1029/1999jd900406
|View full text |Cite
|
Sign up to set email alerts
|

Microphysics and chemistry of sulphate aerosols at warm stratospheric temperatures

Abstract: conditions, improving agreement with measurements. Furthermore, the production of HONO can either enhance gas-phase OH concentrations or promote secondary liquid reactions, including HONO+HNO 3 and HONO+HC1. Primary uncertainties include the uptake coefficient of CH20 relevant to reaction with HNO 3, the amount of HONO available for secondary reaction, and the relative rates of HONO reaction with HNO 3 and HC1. The fate of the formic acid product, whose presence in the stratosphere may be an indicator for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[15] The gas-phase chemistry [Drdla et al, 1999] incorporates 58 species, grouped into 29 families. 188 gas-phase reactions (41 of which are photodissociations) are considered, using rates from the work of Sander et al [2000].…”
Section: Model Descriptionmentioning
confidence: 99%
“…[15] The gas-phase chemistry [Drdla et al, 1999] incorporates 58 species, grouped into 29 families. 188 gas-phase reactions (41 of which are photodissociations) are considered, using rates from the work of Sander et al [2000].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Lightning can produce large amounts of NO [ Jeker et al , 2000], and NO x can be oxidized to HNO 3 over a period of several days by the daytime reaction with OH [ Jaegle et al , 1998]. To evaluate this possibility at tropical tropopause conditions, a chemical trajectory box model [ Drdla et al , 1999] was used to simulate the conversion of lightning‐produced NO to HNO 3 . An initial injection of 3 ppbv NO was assumed, consistent with past observations [ Stith et al , 1999; Jeker et al , 2000].…”
Section: Nitric Acid Concentrations At the Tropical Tropopausementioning
confidence: 99%
“…These were the data from UARS, multiyear observations of column abundance of NO 2 and HNO 3 from the surface, and high spatial resolution in situ measurements of NO y from balloons and aircraft. Extensive model‐measurement comparison were done by several research groups [ Morris et al , 1997; Sen et al , 1998; Danilin et al , 1999; Drdla et al , 1999; Gao et al , 1999]. It was found that NO x /NO y ratios and the NO 2 abundance predicted by the atmospheric models were substantially less than their observed values in the 30 to 7 mbar region.…”
Section: Introductionmentioning
confidence: 99%